PENGARUH MOTIVASI BELAJAR DAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII DI TAMAN DEWASA (SMP) TAMAN SISWA PEMATANGSIANTAR - Cori Elisabet Fidianata Gultom; Anton Luvi Siahaan; Debbi Petra Meyana Sitorus (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem in this research is the low social studies learning outcomes of students in the learning process. This research aims to determine the influence of learning motivation and learning facilities on student learning outcomes in social studies subjects for class VIII at Taman Siswa Pematangsiantar Adult Park (SMP).The variables in this research are learning motivation and learning facilities as independent variables and learning outcomes as the dependent variable. This type of research is quantitative research, with the research population being Class VIII students at Taman Siswa Pematangsiantar Adult School (SMP) consisting of 76 students using nonprobability sampling (saturated sample). The data collection technique uses instruments: (1) Learning Motivation questionnaire, (2) Learning Facilities questionnaire and, (3) Learning Results in the form of mid-semester exam scores.The results of this research show that: (1) There is a negative and significant influence between learning motivation variables on learning outcomes. This result can be seen in the t test where the tcount value of learning motivation shows tcount < ttable, namely -3.866 < 1.669. (2) There is a positive and significant influence between the learning facility variables on learning outcomes, this result is in the t test where the tcount value of learning facilities shows tcount > ttable, namely 3,622 > 1,699.(3) There is a significant influence of learning motivation and learning facilities on learning outcomes. This result can be seen in the F test where the F value is 13,668 > F table 3.12. So based on the calculation results above, it can be concluded that the research results reject the null hypothesis (H03) and accept the alternative hypothesis (Ha3). Thus, together learning motivation and learning facilities influence the learning outcomes of class VIII students in social studies subjects at Taman Siswa Pematangsiantar Adult Park (SMP) can be accepted.The R Square coefficient of determination test was found to be 0.272, equal to 27.2% of the learning motivation variables and learning facilities influencing student learning outcomes at Taman Siswa Pematangsiantar Adult Park (SMP) and the remaining 73% was the influence of other variables not examined in this research. Multiple regression = Y =78,548 – 0.230 x1 + 0.265 X2 + 791,538